Characterization of biochar from pyrolysis of corn residues in a semi-continuous carbonizer - Nakorn Tippayawong (2018)
Copyright © 2018, AIDIC Servizi S.r.l. Thailand is a major agro-industrial country with many economic crops including corn. In northern part of the country, harvesting of corn grain generates massive amounts of agricultural waste, including corn cobs, peels, leaves and stalks. Open burning of biomass is a common practice as a low-cost, low-effort means in disposing of crop residues and controlling weeds in the field. It releases large quantities of particulate and gaseous pollutants to the atmosphere. The practice has significantly negative impact on the environment and human health. These corn residues can be utilized for renewable energy. A promising alternative to burning is carbonization. Carbonization or slow pyrolysis is a thermochemical conversion of solid organic materials at elevated temperature in the absence of air or oxygen. Through thermal decomposition processes, a solid product called biochar as well as gaseous and liquid byproducts are generated. The objectives of this work were to demonstrate a practical production of biochar from corn cobs in a modern semi-continuous carbonizer, and to evaluate its performance in terms of reaction temperatures attained, overall processing time, biochar yields and properties. Experiments were carried out in a retort typed, cylindrical drum mounted horizontally. Its dimension was 1.5 m long with inside diameter of 1.05 m. The carbonizer was externally heated by combustion of solid biomass and pyrolysis gas in a grated furnace. It was also equipped with slowly rotating paddle. For each test, about 90-120 kg of corn cobs was fed into the reactor. Temperatures at various locations inside the carbonization chamber were recorded and used as representative for pyrolysis temperature. The end of operation for a certain condition was determined by checking that combustible gas was no longer released and the pyrolysis flame was no longer sustained. The reactor was then unloaded and the resulting biochar was left to cool down to room temperature in a closed container. Subsequently, the solid char products were collected, weighed and sent for analysis. Large amount of corn cobs was successfully converted to good quality biochar in a semi-continuous carbonization reactor system. The system was shown to operate well. Biochar yields of 23 - 33 % were obtained, with the heating value as high as 24 MJ/kg. The process took around 2.5 h at maximum loading. The study showed that valuable solid products can be obtained from corn cobs via slow pyrolysis process.